Respecting patients' DNR preferences. Issue 5 (27th September 2015) - Crigger, Nancy; Sindt, Jeri
Abstract : This article informs readers of common misconceptions and challenges when applying DNRs to the perioperative setting and reviews formal positions on DNR orders in the perioperative experience.